Penerapan Teknik Dasar Bola Tangan melalui Motivasi Peserta Didik Sekolah Khusus Olahraga (SKO) Riau - Henjilito, Raffly; Makorohim, M. Fransazeli; Widiantoro, Didik; Setiawan, Budi Arif; Amran, Zaiful (Universitas Pahlawan Tuanku Tambusai, 2026)
This Community Service activity aims to improve mastery of basic handball techniques by strengthening the motivation of students at the Riau Special Sports School (SKO). The problem faced by partners is the students' still low understanding and skills regarding basic handball techniques and motivation to participate in training activities. The service implementation method is carried out through an educational and participatory approach, including socialization of handball materials, the meaning of basic techniques, direct practice, training assistance, and providing motivation through varied and fun learning methods. The basic techniques applied include passing, catching, dribbling, shooting, and basic defensive movements. The activity was evaluated through observations of student engagement, assessment of basic technical skills, and student responses during the activity. The results showed increased student motivation, enthusiasm, and active participation, which positively impacted their mastery of basic handball techniques. Therefore, this community service activity makes a significant contribution to supporting handball achievement development at SKO Riau and can be used as a practical learning and training model for coaches and sports educators.